Molecular dynamics simulations of carbon dioxide hydrate growth in electrolyte solutions of NaCl and MgCl2 - Yi, Lizhi; Liang, Deqing; Zhou, Xuebing; Li, Dongliang; Wang, Jianwei (Molecular Physics, 2014)
Molecular dynamics simulations are performed to study the growth of carbon dioxide (CO2) hydrate in electrolyte solutions of NaCl and MgCl2. The kinetic behaviour of the hydrate growth is examined in terms of cage content, density profile, and mobility of ions and water molecules, and how these properties are influenced by added NaCl and MgCl2. Our simulation results show that both NaCl and MgCl2 inhibit the CO2 hydrate growth. With a same mole concentration or ion density, MgCl2 exhibits stronger inhibition on the growth of CO2 hydrate than NaCl does. The growth rate of the CO2 hydrate in NaCl and MgCl2 solutions decreases slightly with increasing pressure. During the simulations, the Na+, Mg2+, and Cl- ions are mostly excluded by the growing interface front. We find that these ions decrease the mobility of their surrounding water molecules, and thus reduce the opportunity for these water molecules to form cage-like clusters toward hydrate formation. We also note that during the growth processes, several 5(12)6(3) cages appear at the hydrate/solution interface, although they are finally transformed to tetrakaidecahedral (5(12)6(2)) cages. Structural defects consisting of one water molecule trapped in a cage with its hydrogen atoms being attracted by two Cl- ions have also been observed.